2020
DOI: 10.1183/13993003.00980-2019
|View full text |Cite
|
Sign up to set email alerts
|

The Pleural Effusion And Symptom Evaluation (PLEASE) study of breathlessness in patients with a symptomatic pleural effusion

Abstract: IntroductionPathophysiology changes associated with pleural effusion, its drainage and factors governing symptom response are poorly understood. Our objective was to determine: 1) the effect of pleural effusion (and its drainage) on cardiorespiratory, functional and diaphragmatic parameters; and 2) the proportion as well as characteristics of patients with breathlessness relief post-drainage.MethodsProspectively enrolled patients with symptomatic pleural effusions were assessed at both pre-therapeutic drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 41 publications
2
59
0
6
Order By: Relevance
“…We read with interest the article entitled 'Role of early definitive management for newly diagnosed malignant pleural effusion related to lung cancer' by Chiang et al 1 We have been particularly interested in the management of pleural effusion in patients with lung cancer, [2][3][4] and we would like to raise four issues arising from the article by Chiang et al…”
Section: To the Editorsmentioning
confidence: 99%
See 4 more Smart Citations
“…We read with interest the article entitled 'Role of early definitive management for newly diagnosed malignant pleural effusion related to lung cancer' by Chiang et al 1 We have been particularly interested in the management of pleural effusion in patients with lung cancer, [2][3][4] and we would like to raise four issues arising from the article by Chiang et al…”
Section: To the Editorsmentioning
confidence: 99%
“…First, in table 1 of Chiang et al's study, 1 the authors showed that 154 patients had targetable oncogenic mutations (142 patients, excluding patients with uncommon epidermal growth factor receptor (EGFR) mutations). How did the authors treat the 12 patients with uncommon EGFR mutations?…”
Section: To the Editorsmentioning
confidence: 99%
See 3 more Smart Citations